2013
DOI: 10.1371/journal.pone.0075291
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Assessment of Pollen- and Seed-Mediated Gene Flow from Genetically Engineered Plum Prunus domestica

Abstract: Pollen flow from a 0.46 ha plot of genetically engineered (GE) Prunus domestica located in West Virginia, USA was evaluated from 2000–2010. Sentinel plum trees were planted at distances ranging from 132 to 854 m from the center of the GE orchard. Plots of mixed plum varieties and seedlings were located at 384, 484 and 998 m from the GE plot. Bee hives (Apis mellifera) were dispersed between the GE plum plot and the pollen flow monitoring sites. Pollen-mediated gene flow from out of the GE plum plot to non-GE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 40 publications
4
29
1
Order By: Relevance
“…Similar to other studies (Fitzpatrick et al, 2003; Teuber et al, 2004; Fitzpatrick et al, 2007a; Hagler et al, 2011; Rieben et al, 2011; Scorza et al, 2013; Dong et al, 2016), results from our quadratic regression indicated that AP significantly decreased as the distance from GE fields increased. Results from our spatial prediction map showed similar results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to other studies (Fitzpatrick et al, 2003; Teuber et al, 2004; Fitzpatrick et al, 2007a; Hagler et al, 2011; Rieben et al, 2011; Scorza et al, 2013; Dong et al, 2016), results from our quadratic regression indicated that AP significantly decreased as the distance from GE fields increased. Results from our spatial prediction map showed similar results.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas exponential decay models have been used to study the movement of transgenes into non‐GE crops (Fitzpatrick et al, 2003; Teuber et al, 2004; Hagler et al, 2011; Scorza et al, 2013; Dong et al, 2016), we elected to use a quadratic regression approach, which has fewer assumptions and can assume a wider variety of decay shapes than an exponential model. We used a logit transformation on proportion of AP, log[ p /(1 − p )], where a small amount of positive noise was added to zero counts to avoid taking the log of zero.…”
Section: Methodsmentioning
confidence: 99%
“…Pollinator activity may be adversely affected by low temperatures and excessive rainfall during bloom (Scorza et al, 2013). Excessive rainfall may also hinder the diffusion of floral nectar scent (Yan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Gene flow was detected in only four of the 11 years and then in only 0.31% of over 12,000 seeds tested. The results of the study suggested that a 400-m distance from non-GE plums would allow for coexistence (Scorza et al 2013b). Bees were considered the most likely vector for pollen movement.…”
Section: Ge Plumsmentioning
confidence: 87%
“…The results of the study suggested that a 400‐m distance from non‐GE plums would allow for coexistence (Scorza et al. ). Bees were considered the most likely vector for pollen movement.…”
Section: Ge Plumsmentioning
confidence: 99%